Incidence density and relative rate assessment of knee osteoarthritis with respect to BMI, age and gender conducted in a tertiary care hospital in Hyderabad, India - Aseem, Syed; Khanam, Fouqia Mahnaz; Ghori, Syed Hafeezuddin; Sufiyanuddin, M. D.; Yaseen, M. A. Malik (International Journal Of Community Medicine And Public Health, 2023)
Background: Osteoarthritis is the most common form of arthritis associated with limitation in mobility. Weight bearing joints of axial and peripheral skeleton are primarily affected. Prevalence of symptomatic knee osteoarthritis among men and women is 10% and 13%. Ageing and obesity epidemic are the leading causes for development of osteoarthritis in a given population. Methods: The study was conducted at a tertiary care hospital in Hyderabad, India. Data was gathered from orthopedic department on a daily basis during the study duration. Patients with any grade of Kellgren-Lawrence scale of knee osteoarthritis were included in the study and incidence density, relative rate, p-value were assessed. Results: During the study course, a total of 100 patients were enrolled. Overweight, obese and healthy patients contributed to 51%, 33% and 16% of incidence density with relative rate as 1.04, 0.49 and 0.19 respectively (p-value=0.042). Incidence density of patients ≥45 years and <45 years was 83% and 17% with relative rate as 4.9 and 0.2 (p value<0.0001). Incidence density in males and females was 34% and 66% with relative rate as 1.94 and 0.51 (p-value<0.0001). The data analyzed is statistically significant. Conclusions: A direct proportionality between people exceeding normal BMI range and progression of knee osteoarthritis is observed due to strain manifested on diarthrodial joint by overweight patients. Increase in age is associated with onset of knee osteoarthritis because of age related-changes seen in cartilage and loss of chondrocytes. Women are more affected with knee osteoarthritis when compared to men due to irregularities in hormones post-menopause.